Comparison of ultrasound and UV technologies to control bulking and foaming in a wastewater treatment facility. A case study in an industrial park in Morelos, Mexico - Hernández-Romano, Jesús; Trevino-Quintanilla, Luis; Guillén-Garcés, Angélica; Barragán-Trinidad, Martín; Bustos-Terrones, Victoria; Díaz de Anda, Diana K.; Moeller-Chávez, Gabriela (Frontiers in Environmental Science, 2022)
Most wastewater treatment plants use activated sludge-based biological systems for this purpose. The latter must effectively remove organic matter and, at the same time, show good sedimentability. However, sometimes there is an excessive proliferation of certain bacteria, giving rise to filamentary swelling, compromising the excellent sedimentability of the sludge. In this sense, the study’s objective was to evaluate the effect of applying two different technologies, the application of low-frequency ultrasound and UV radiation. Some bench-scale experiments were performed using the bulked sludge from the secondary clarifier of a wastewater treatment facility in an industrial park (CIVAC) in Morelos, Mexico, affected by filamentous organisms. Results showed that for the UV application for two, four, and 6 min, the settleability of the mixed liquor suspended solids was not improved; on the other hand, the cavitation effect caused by the ultrasound application demonstrated effective action against the destruction of filamentous organisms. The 10 min condition showed a significant decrease in the filament integrity of the microorganisms and a significant improvement of sedimentation velocity and sludge volume index (SVI) values and settleability of the sludge, but not enough to satisfy national discharge regulations related to total suspended solids in the treated effluent. Molecular identification indicates the presence of the genera Thauera and Brevundimonas in the sludge.